Guai guai bu pa da zhen - Chen, Zhiyuan 1975- (Hui ben, 2018)
Guai Guai is sick and has to go to hospital. He gets so afraid when he hears other children cry while being given an injection. Is it really so horrible? Does it really hurt so much?